Uterine Tumor Resembling Ovarian Sex Cord Tumor (UTROSCT): A Morphologic and Molecular Study of 26 Cases Confirms Recurrent NCOA1-3 Rearrangement. (January 2020) - Goebel, Emily A.; Hernandez Bonilla, Silvia; Dong, Fei; Dickson, Brendan C.; Hoang, Lien N.; Hardisson, David; Lacambra, Maribel D.; Lu, Fang-I; Fletcher, Christopher D.M.; Crum, Christopher P.; Antonescu, Cristina R.; Nucci, Marisa R.; et al.
Abstract : Uterine tumor resembling ovarian sex cord tumor (UTROSCT) is a rare mesenchymal neoplasm, of uncertain biological potential, that was recently reported to exhibit recurrent gene fusions involving NCOA2-3 . The purpose of this study was to, using a larger sample size, better characterize the histopathologic and molecular diversity of UTROSCT. Twenty-six cases of UTROSCT from 5 institutions were selected for further study. Fluorescence in situ hybridization for NCOA1, NCOA2, NCOA3, ESR1 and GREB1, and targeted RNA sequencing was performed on 17 and 8 UTROSCTs, respectively. Eight cases underwent massively parallel sequencing to detect single nucleotide variants (SNV), copy number variations, and structural variants using a targeted hybrid-capture based assay. NCOA1-3 rearrangement was identified in 81.8% (18/22) of cases. The most common fusion was ESR1-NCOA3, occurring in 40.9% (9/22). GREB1-NCOA1 (n=4), ESR1-NCOA2 (n=3), and GREB1-NCOA2 (n=1) rearrangements were also identified. No recurrent SNVs were identified and no tumor had SNVs in FOXL2, DICER1, STK11, or AKT1, which can be seen in ovarian sex cord-stromal tumors. Copy number variations were infrequent. Clinical follow-up was available for 11 cases with a mean follow-up interval of 94.4 (range, 1 to 319) months. Only one case had a recurrence 66 months after the initial diagnosis and this was the single case with a GREB1-NCOA2 fusion. This study reports the morphologic spectrum of UTROSCT and confirms the recently reported recurrent NCOA2-3 gene fusions, in addition to identifying novel rearrangements involving NCOA1 in these tumors. Abstract : Supplemental Digital Content is available in the text.